S73 Trends in empyema in Scottish Children 2000–2011. (14th November 2013) - Nath, S; Turner, SW
Abstract : Background: An abrupt rise in empyema prevalence in children was noted in the UK and other countries during the late 1990s and early 2000s. Time trends in empyema prevalence in Scotland has not been described since 2005 at a time when prevalence appeared to be still rising 1 . A number of factors may have changed empyema prevalence since 2005 including the 2006 smoking ban and introduction of heptavalent (2006) and 13-valent (2010) pneumococcal vaccinations. Here we applied our previous methodology 1 to test the hypothesis that the prevalence of childhood empyema continues to rise beyond 2005. Methods: This was a whole population study of 2000–2011 hospital admissions using ICD-10 diagnostic codes. As previously we captured admissions for pneumonia and croup to detect increasing prevalence of admissions with other respiratory presentations. Results: Over this 12 year period there were 398 cases of empyema. The prevalence rose from 22cases/million in 2000 to 55 cases/million in 2011 (see figure), equivalent to a rise of 4 cases/million/year (R 2 = 0.81 p = 0.002). Within the 1–4 year age range, empyema prevalence rose by 10 cases/million/year (R 2 = 0.86 p < 0.001) whilst prevalence did not change for the under 1 and 10–14 year old age range. The prevalence of croup and pneumonia for did not change during 2000–2011 suggesting that increased empyema prevalence did not reflect increasing respiratory admissions or increasing pneumonia prevalence. Conclusion: The prevalence of empyema in Scottish children has continued to rise beyond 2005 and the reason for this is not clear. Public health initiatives introduced since 2005 do not appear to have altered empyema prevalence in children. References: Roxburgh cs et al . Trends in pneumonia and empyema in Scottish children in the past 25 years. Arch Dis Child 2008;93:316–8.